Pengaruh Career Development dan Organizational Culture terhadap Job Satisfaction serta Dampaknya pada Employee Performance - Putra, Johan Yuda Prawira (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
The purpose of this study is to identify and test the effect of career development and organizational culture on performance through job satisfaction in banking employees in the South Jakarta area. 38 employees were participating, while the questionnaire processed using Partial Least Square. The results prove organizational culture and career development can influence the level of employee satisfaction. Next, if seen from its influence on performance, only organizational culture affects, while satisfaction and career development do not affect. If based on its influence through job satisfaction, organizational culture and career development do not affect. The implication that can be practiced by companies is objectivity in promotion with based on aspects of performance and optimize organizational culture that has been applied in the company and researchers suggest that companies can create programs that can increase dedication, loyalty, and employee commitment to work such as providing rewards, providing clear career paths, and better HR management.